Depredación del piojo rojo de California, 'Aonidiella aurantii' (Maskell) por fitoseidos depredadores - Juan-Blasco, María; Verdú, María J.; Urbaneja, Alberto (2017)
For our knowledge, there are few studies about the role of phytoseiids (Acari: Phytoseiidae) preying on Aonidiella aurantii (Maskell) (Hemiptera: Diaspididae) crawlers. The aims of the present work were to study in laboratory the development of three of the most abundant phytoseiids in citrus in Spain, Euseius stipulatus (Athias- Henriot), Neoseiulus californicus (McGregor) and Typhlodromus phialatus Athias- Henriot, and of the recently introduced and released in Spain, Amblyseius swirskii Athias-Henriot, feeding exclusively on A. aurantii crawlers. Furthermore, the ability of A. swirskii to reduce A. aurantii infestation on young citrus plants was studied under semi-field conditions by means of augmentative releases of this phytoseiid.Females of E. stipulatus were the only phytoseiid species tested which were not able to lay eggs on this prey. The progeny of N. californicus were not able to reach the protonymphal stage. On the other hand, T. phialatus and A. swirskii completed their development, from egg to adult preying exclusively on this prey. In the semi-field experiments, several doses of A. swirskii were tested. Once the phytoseiids were installed on the young trees, an artificial infestation of A. aurantii crawlers was promoted in each citrus plant. A significant reduction of A. aurantii infestation was observed on those trees where A. swirskii was previously released.; Hasta la fecha, no existen prácticamente estudios a cerca del papel de los fitoseidos como depredadores de ninfas móviles del piojo rojo de California, Aonidiella aurantii (Maskell). Los objetivos del presente trabajo fueron estudiar en laboratorio el desarrollo de tres de los fitoseidos más abundantes en los cítricos españoles, Euseius stipulatus (Athias-Henriot), Neoseiulus californicus (McGregor) y Typhlodromus phialatus Athias-Henriot y del recientemente introducido en España, Amblyseius swirskii Athias- Henriot alimentados exclusivamente de ninfas móviles de A. aurantii y además, estudiar en condiciones de semicampo las posibilidades de reducción de las poblaciones de A.aurantii mediante liberaciones inoculativas de A. swirskii.Las hembras de E. stipulatus no fueron capaces de realizar la puesta alimentadas exclusivamente de ninfas móviles de A. aurantii mientras que las otras tres especies de fitoseidos sí. Los individuos descendientes de N. californicus no lograron alcanzar el estadio de protoninfa. Por el contrario, T. phialatus y A. swirskii completaron su desarrollo hasta adulto. En los experimentos de semicampo, se liberaron varias dosis de A. swirskii sobre plantones de clementinos. Una vez instalados sobre el plantón se procedió a su infestación con ninfas móviles de A. aurantii. Se observó una reducción significativa de la infestación de A. aurantii en los plantones sobre los cuales se había liberado A. swirskii.